An integrated experimental and physiologically based pharmacokinetic modeling study of penicillin G in heavy sows. Issue 4 (23rd April 2019) - Li, Miao; Mainquist‐Whigham, Christine; Karriker, Locke A.; Wulf, Larry W.; Zeng, Dongping; Gehring, Ronette; Riviere, Jim E.; Coetzee, Johann F.; Lin, Zhoumeng
Abstract: Penicillin G is widely used in food‐producing animals at extralabel doses and is one of the most frequently identified violative drug residues in animal‐derived food products. In this study, the plasma pharmacokinetics and tissue residue depletion of penicillin G in heavy sows after repeated intramuscular administrations at label (6.5 mg/kg) and 5 × label (32.5 mg/kg) doses were determined. Plasma, urine, and environmental samples were tested as potential antemortem markers for penicillin G residues. The collected new data and other available data from the literature were used to develop a population physiologically based pharmacokinetic (PBPK) model for penicillin G in heavy sows. The results showed that antemortem testing of urine provided potential correlation with tissue residue levels. Based on the United States Department of Agriculture Food Safety and Inspection Service action limit of 25 ng/g, the model estimated a withdrawal interval of 38 days for penicillin G in heavy sows after 3 repeated intramuscular injections at 5 × label dose. This study improves our understanding of penicillin G pharmacokinetics and tissue residue depletion in heavy sows and provides a tool to predict proper withdrawal intervals after extralabel use of penicillin G in heavy sows, thereby helping safety assessment of sow‐derived meat products.